Calcium intake and the associations with faecal fat and energy excretion, and lipid profile in a free-living population. (19th September 2017) - Kjølbæk, Louise; Lorenzen, Janne K.; Larsen, Lesli H.; Astrup, Arne
Abstract: The aim of the present study was to investigate the associations between the habitual Ca intake and faecal fat and energy excretion as well as blood lipid profile in free-living normal-weight and overweight individuals. The participants were enrolled for an 8-d period where data from a 7-d diet registration (days 1–7), a 5-d faeces collection (days 3–7), a 2-d urine collection (days 5–7), and anthropometric measurements and a fasting blood sample (day 8) were collected. Analyses showed that dietary Ca intake (g/10 MJ per d) was positively associated with excretion of faecal fat ( P  = 0·004) and energy ( P  = 0·031) when adjusted for BMI, age, sex and intake of Ca-containing supplements. However, after adjustment for intake of fibre, the effect of Ca intake disappeared. Nevertheless, total cholesterol (CHOL) and LDL-CHOL concentrations were associated negatively with Ca intake ( β −0·62 (95 % CI −0·96, −0·28) mmol/l, P  < 0·001, and β −0·49 (95 % CI −0·78, −0·20) mmol/l, P  = 0·001, respectively, per 1000 mg/10 MJ per d increase in Ca intake). In conclusion, incorporation of Ca-rich food products in a habitual diet was associated with reduced total CHOL and LDL-CHOL concentrations, which may lower the risk of CVD in the long term.